A genetic diversity assessment of starch quality traits in rice landraces from the Taihu basin, China - Yan AO; Yong XU; Xiao-fen CUI; An WANG; Fei TENG; Li-qun SHEN; Qiao-quan LIU (Journal of Integrative Agriculture, 2016)
There are nearly 1000 rice landrace varieties in the Taihu basin, China. To assess the genetic diversity of the rice, 24 intragenic molecular markers (representing 17 starch synthesis-related genes) were investigated in 115 Taihu basin rice landraces and 87 improved cultivars simultaneously. The results show that the average genetic diversity and polymorphism information content values of the landraces were higher than those of improved cultivars. In total, 41 and 39 allele combinations (of the 17 genes) were derived from the landraces and improved cultivars, respectively; only two identical allele combinations were found between the two rice variety sources. Cluster analysis, based on the molecular markers, revealed that the rice varieties could be subdivided into five groups and, within these, the japonica improved rice and japonica landrace rice varieties were in two separate groups. According to the quality reference criteria to classify the rice into grades, some of the landraces were found to perform well, in terms of starch quality. For example, according to NY/T595-2002 criteria from the Ministry of Agriculture of China, 25 and 33 landraces reached grade 1, in terms of their apparent amylose content and gel consistency. The varieties that had outstanding quality could be used as breeding materials for rice quality breeding programs in the future. Our study is useful for future applications, such as genetic diversity studies, the protection of rice variety and improvment of rice quality in breeding programs.